Behaviour of loose sand treated using bio-gelation method - Wang, Kangda (2022)
Bio-gelation is a new method for improving the hydraulic and mechanical properties of sandy soil through the production of polymeric gel to fill in the pores of soil. In this paper, a study on the engineering behaviour of loose sand treated using this method is presented. A series of permeability and undrained monotonic and cyclic triaxial tests were carried out on both clean sand and bio-gelled sand. The test results showed that the coefficient of permeability was reduced by 3 to 4 orders of magnitude in the bio-gelled sand samples, and the higher the alginate concentration, the lower the permeability. In the monotonic triaxial tests, sand samples that would have liquefied under static conditions manifested strain-hardening behaviour after treatment. The shear strength of the bio-gelled sand also increased as was indicated by an increase in the slope of the failure line from 1.08 to 1.27. In the cyclic triaxial tests, the number of cycles at failure increased from 183 for clean sand to 485 for bio-gelled sand, and the excess pore water pressure response was also much reduced. The hydrogel produced by the bio-gelation process was stable under both hydrostatic and seepage conditions. The other advantages of the bio-gelation method include 1) the massive formation of hydrogel can be controlled to be 28 hours later after injection, 2) the pH value of soil fluid can be maintained at neutral and 3) it is cost-effective for liquefaction or seepage control for sand compared with other conventional methods.